ANALISIS PENGARUH KINERJA KEUANGAN DAN NILAI TUKAR TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR - Ashwa, Anya Peditha (Journal of Financial Economics & Investment, 2023)
The purpose of this study is to analyze the effect of financial performance and exchange rates on stock prices in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021. The method used in this study is multiple linear regression analysis on panel data using the Eviews 9 analysis tool and using a quantitative approach sourced from IDX data used by 95 companies and 3 manufacturing industry sectors. The results of this study are based on the F test that the variables CR, ROE, DER, PER & exchange rates have a joint effect on stock prices. Whereas in the t test (partial) the variable Return on equity (ROE) affects stock prices. This shows that CR has a positive and insignificant effect on stock prices, ROE & DER have a significant positive effect on stock prices, then PER & Exchange rates have a negative and insignificant effect so that it will have a positive impact on manufacturing companies where these companies are able to reduce the impact caused by the depreciation of the Indonesian exchange rate.